'Tick the box and move on': compartmentalization and the treatment of the environment in decision‐making processes. (6th August 2021) - SMYTH, CAER
Abstract: Legal decision‐making processes are contending with increasingly urgent and complex environmental issues. While the importance of treating these issues holistically has long been recognized in environmental law, obstacles seem to exist that block decision makers in the planning system from taking integrated approaches to environmental issues. This article approaches this problem from a grounded perspective. It draws on original empirical research findings from a socio‐legal ethnographic research project conducted at a public local inquiry in South Wales (the inquiry into the M4 Corridor around Newport scheme). The article suggests that embedded assumptions in legal decision‐making processes might partly account for this often limited response. It proposes that such processes tend to 'compartmentalize' and that this tendency has an adverse impact on the treatment of the environment, holding back efforts within environmental law that seek to embed more holistic approaches to environmental decision making.